2021
DOI: 10.24843/ejmunud.2021.v10.i08.p01
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Pengumuman Penurunan Harga BBM Terhadap Abnormal Return Pada Perusahaan Yang Tergabung Dalam Idx30

Abstract: Salah satu informasi yang sangat berpengaruh terhadap perekonomian Indonesia adalah kebijakan pemerintah untuk menurunkan harga Bahan Bakar Minyak (BBM). Studi ini bertujuan untuk mengetahui pengumuman penurunan harga BBM dapat menciptakan perolehan Abnormal return yang signifikan sebelum, saat dan sesudah pengumuman penurunan harga BBM tanggal 31 januari 2020. Penelitian ini dilakukan pada perusahaan yang masuk dalam IDX30 dengan menggunakan metode sensus mendapatkan jumlah sampel sebanyak 15 perusahaan. Peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Study (Utami & Purbawangsa, 2021)researching the companies included in the IDX30 using the census method obtained a total sample of 15 companies. found results that there were no significant abnormal returns during the event period so that there was no market reaction around the announcement period while the research (Dirga et al, 2022) There is no significant difference in average abnormal return between the period before and after the announcement of the fuel price increase, there is no significant difference in the average trading volume activity between before and after the announcement of the fuel price increase.…”
Section: Discussionmentioning
confidence: 99%
“…Study (Utami & Purbawangsa, 2021)researching the companies included in the IDX30 using the census method obtained a total sample of 15 companies. found results that there were no significant abnormal returns during the event period so that there was no market reaction around the announcement period while the research (Dirga et al, 2022) There is no significant difference in average abnormal return between the period before and after the announcement of the fuel price increase, there is no significant difference in the average trading volume activity between before and after the announcement of the fuel price increase.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Febriyanti & Rahyuda (2016) discovered the announcement of the fuel price escalation that occurred at the beginning of the Jokowi and Jusuf Kalla administrations showed significant differences in TVA and abnormal return of companies including LQ 45 before and after the announcement of the fuel price increase, but there was no significant change in TVA or abnormal return of the industry including LQ 45 Before and after the announcement of the fuel price reduction. Utami & Purbawangsa (2021) found the results of the 2020 fuel price reduction event showed no significant difference in the abnormal return of companies listed on the IDX 30 before and after the 2020 fuel price reduction event. Other studies such as those conducted by Anita & Veronica (2016) found no difference in abnormal returns and TVA on fuel price increases during the Susilo Bambang Yudhoyono administration.…”
Section: Introductionmentioning
confidence: 90%
“…Studies on this topic have been discussed by several previous researchers, including Laksmi & Ratnadi (2015); Febriyanti & Rahyuda (2016); Choriliyah et al, (2016); Utami & Purbawangsa (2021); Tiswiyanti & Asrini (2015); Anita & Veronica (2016); Femianita & Asandimitra (2014); Chandra (2013); Liogu & Saerang (2015); Fitriaty & Saputra (2022). First, Laksmi & Ratnadi (2015) discovered the announcement of a fuel price decrease that occurred specifically on January 1, 2015, found no difference in abnormal returns of transportation companies between before and after the announcement of the decrease occurred.…”
Section: Introductionmentioning
confidence: 97%
“…Penelitian tersebut menyebutkan bahwa tidak terjadi abnormal return signifikan yang diukur dalam periode lima harian di sekitar pengumuman. Disebutkan bahwa hal ini terjadi sebab perubahan harga BBM merupakan informasi yang terbuka secara publik serta dianggap telah direncanakan secara matang, sehingga investor menyimpulkan bahwa informasi tersebut tidak memiliki dampak terhadap perekonomian dan tidak merespon ke pergerakan saham (Utami & Purbawangsa, 2021). Selain itu, penelitian Saputra, Purbawangsa, dan Artini (2017) juga menyebutkan tidak terjadinya abnormal return signifikan selama rentang waktu penagamatan.…”
Section: Idxnoncycunclassified